Praktik Perjanjian Konsinyasi Rumah Produksi Kerupuk Ikan Tenggiri Jombang Perspektif Hukum Bisnis Syariah - Siti Ainur Rosyida (Kampus Akademik Publiser, 2024)
In true human life, one can never be separated from the name muamalah to fulfill all one's life. Muamalah is a person's association, everyone who carries out actions in relation to other people which will later give rise to rights and obligations. This activity of buying and selling or storing goods (consignment) is a form of helping someone who will later get maximum benefits or results from each other. And mutually get elements that are mutually helpful between fellow humans on this earth, because we are encouraged to help each other or help each other in life. Based on the background above, the problems that arise are (1) What is the practice of consignment agreements for the Jombang Mackerel Fish Crackers Production House? (2) What is the perspective of Sharia Business Law on the Practice of Consignment Agreements for Tenggiri Fish Cracker Production Houses? The objectives are (1) To find out and study the practice of consignment agreements for Tenggiri Fish Cracker Production Houses in Jombang. (2) To find out the perspective of Sharia Business Law 'ah in the practice of the Jombang Tenggiri Fish Crackers Production House consignment agreement.